ANALISIS PEMBERDAYAAN PEREMPUAN PADA KINERJA USAHA GUNA MENDUKUNG INOVASI UMKM KOPERASI WANITA SERUNI PUTIH - Eni Nur Hayati; Melvin Rahma Sayuga Subroto (DAS Institute, 2023)
This study aims to analyze how empowering women in the business performance of the Seruni Putih Women's Cooperative and to find out the efforts and solutions for the performance of SMEs to support innovation of SMEs in Kopwan Seruput. The research method used in this research is a qualitative method. This research is included in the type of research case study and is descriptive. The results of the study indicate that business performance has increased. The increase was not only from increased sales, capital growth, market developments, additional workforce and increased profits. However, it can be from creation or innovation which was created by the mothers of herbal medicine business owners. Business performance efforts to support innovation of SMEs include openness in thinking, sharing experiences and participating in training activities.